Probiotics, a promising therapy to reduce the recurrence of bacterial vaginosis in women? a systematic review and meta-analysis of randomized controlled trials - Chieng, Wei Keong; Abdul Jalal, Muhammad Irfan; Bedi, Jashveerdeep Singh; Zainuddin, Ani Amelia; Mokhtar, Mohd Helmy; Abu, Muhammad Azrai; Chew, Kah Teik; Nur Azurah, Abdul Ghani (Frontiers in Nutrition, 2022)
Introduction: The evidence for probiotics efficacy in preventing BV recurrences among women aged 18 years and above is sparse. We aimed to ascertain the efficacy of probiotics in preventing BV recurrences after at least one menstrual cycle in this population. Method: We conducted a systematic literature search using PubMed, MEDLINE (Ovid interface), Web of Science (WoS), Scopus, EMBASE, ProQuest Dissertations & Theses Global, Cochrane Library databases and registries comprised of Open Science Framework (OSF) preprints registry, the ClinicalTrials.gov (USA), WHO International Clinical Trials Registry Platform (WHO-ICTRP), International Standard RCT Number (ISRCTN) registry, limited to randomized clinical trials in English published between January 2000 and December 2021. The inclusion criteria were trials that administered probiotics to BV-positive women in an experimental arm of at least 20 samples. The usage of probiotics should be preceded with standard antibiotics regimen, and followed by a reassessment of BV status after at least a single menstrual cycle. Risk of bias assessment was completed using Revised Cochrane risk-of-bias tool for randomized trials (RoB 2). The PROSPERO registration number of the review is CRD42022302044. Results: From 8162 identified records, we included 10 studies (n=1234 participants) for final analysis. 7 trials compared probiotics versus placebo; while 3 trials compared probiotics versus metronidazole alone. Using random-effects meta-analysis, probiotics was shown to reduce the risk of BV recurrences by 45% compared to either placebo or metronidazole (14.8% vs 25.5%, RR:0.55 [95%CI: 0.33, 0.91], p=0.03, I2=45.4% [95%CI:0-73.7%]). Sensitivity analysis revealed the robustness of results upon removal of studies with high risk of bias (RR: 0.54 [95%CI: 0.38, 0.77], p=0.006) and reporting bias (RR: 0.53, 95%CI: 0.39, 0.74, p=0.002). Meta regression demonstrated that the route of administration (pvaginal=0.67; poral=0.44), the total dosage of probiotics (p=0.17), cumulative days of probiotics administration (p=0.76) and the number of species in probiotics preparation (p=0.40) were not linked to BV recurrences. Interpretation: Probiotics were associated with more than twofold reduction in BV recurrences when BV status was assessed after at least 1-month post intervention. Further studies should evaluate probiotics effectiveness for BV prevention in a community setting.